The development and validation of the comprehensive assessment of Acceptance and Commitment Therapy processes (CompACT) - Francis, Ashley (2016)
Valid and reliable measures of Acceptance and Commitment Therapy's (ACT) purported mechanism(s) of change are paramount in establishing its incremental validity above other extant psychological therapies. However, the most widely used general measure of psychological flexibility and the six ACT processes of which it is composed of, the Acceptance and Action Questionnaire (AAQ-II), has been significantly criticised, principally in terms of being a conflated distress measure due to having items with poor face and content validity. Theoretically, there has also been debate about whether ACT's 'hexaflex' model, which conceptually underpins the AAQ-II and other ACT process measures, is comprised of fewer than six distinct processes as per current ACT theory. The overall aim of our study was therefore to: 1) develop a new general measure of ACT processes; 2) test the measure's validity and reliability; and 3) establish whether the measure's factor structure accords with Hayes et al.'s (2011) clustering of ACT's six processes into three dyadic processes. The measure was named the Comprehensive assessment of ACT processes ('CompACT').